2009
DOI: 10.1097/tld.0b013e3181a72084
|View full text |Cite
|
Sign up to set email alerts
|

Language and Literacy Development in Individuals With Velo-cardio-facial Syndrome

Abstract: Velo-cardio-facial syndrome (VCFS) is a genetic disorder caused by a microdeletion of chromosome 22q11.2. Although there is some variability, VCFS is associated with a characteristic physical, behavioral, and cognitive phenotype. This review article focuses on aspects of language and literacy development in VCFS, describing what is known and offering avenues for future research. The most consistently reported language and literacy findings in the VCFS population include reading, spelling, phonological processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 119 publications
0
9
2
Order By: Relevance
“…Speech problems, such as hypernasality, are common in 22q11DS (Baylis & Shriberg, 2019;Solot et al, 2019). Especially below the age of 5 years, the majority of children with 22q11DS have poor speech intelligibility (Antshel et al, 2009;Persson et al, 2003;Solot et al, 2000). The exact cause of poor intelligibility in 22q11DS often remains unclear, as it may be the result of a variety of neurological problems, such as dyspraxia or a speech sound disorder, and/or anatomical abnormalities, including velopharyngeal insufficiency in the absence of a cleft palate (Baylis & Shriberg, 2019;Gerdes et al, 1999;Golding-Kushner, 2005;Jackson et al, 2019;Persson et al, 2003;Solot et al, 2019).…”
Section: The Relationship Between Speech and Language In 22q11dsmentioning
confidence: 99%
See 1 more Smart Citation
“…Speech problems, such as hypernasality, are common in 22q11DS (Baylis & Shriberg, 2019;Solot et al, 2019). Especially below the age of 5 years, the majority of children with 22q11DS have poor speech intelligibility (Antshel et al, 2009;Persson et al, 2003;Solot et al, 2000). The exact cause of poor intelligibility in 22q11DS often remains unclear, as it may be the result of a variety of neurological problems, such as dyspraxia or a speech sound disorder, and/or anatomical abnormalities, including velopharyngeal insufficiency in the absence of a cleft palate (Baylis & Shriberg, 2019;Gerdes et al, 1999;Golding-Kushner, 2005;Jackson et al, 2019;Persson et al, 2003;Solot et al, 2019).…”
Section: The Relationship Between Speech and Language In 22q11dsmentioning
confidence: 99%
“…For children with 22q11DS, it has indeed been suggested that parents may be less likely to reinforce early speech attempts if their child has poor speech intelligibility (Shprintzen, 2000). Poor speech intelligibility may thus hamper language development in young children with 22q11DS, as poor intelligibility can negatively affect interactions, thereby reducing their exposure to linguistic input, as well as limit opportunities to practice their language skills (Antshel et al, 2009).…”
Section: The Relationship Between Speech and Language In 22q11dsmentioning
confidence: 99%
“…With an incidence of one in 4000 live births, the 22q11.2 deletion syndrome (22q11.2DS) is the most common microdeletion syndrome (Botto et al, 2003;McDonald-McGinn & Sullivan, 2011). This syndrome, caused by a microdeletion on the long arm of chromosome 22, is phenotypically characterised by a (submucosal) cleft palate, heart abnormalities, some subtle facial features and a specific phenotype with various motor, neurocognitive, behavioural and communicative characteristics (e.g., Antshel, Marrinan, Kates, Fremont, & Shprintzen, 2009;Golding-Kushner, Weller, & Shprintzen, 1985;Prinzie et al, 2002;Solot et al, 2001;Swillen, Vogels, Devriendt, & Fryns, 2000). Description of impaired speech intelligibility caused by velopharyngeal insufficiency has been central in the research on communicative disorders in children with 22q11.2DS.…”
Section: Introductionmentioning
confidence: 99%
“…Two groups whose communicative contributions are also characterised by several pragmatic deficits are those with 22q11.2 deletion syndrome (22q11.2DS; Antshel, Marrinan, Kates, Fremont, & Shprintzen, 2009) and those with Williams syndrome (WS; Brock, 2007). Antshel et al (2007) described that 41% of children with 22q11.2DS met liberal criteria for autism on the Autism Diagnostic Interview-Revised.…”
Section: Cross-syndrome Research On Conversational Skillsmentioning
confidence: 99%